Reading Assignment: Group Work, Impacts on Students’ Reading Comprehension - Dwi Sloria Suharti (Globish: An English-Indonesian Journal for English, Education, and Culture, 2019)
The objective of the research was to know the differences between the ninth grade students of SMPN 1 Rajeg in reading comprehension used group work technique and those used conventional method. The research was conducted to the ninth grade students of SMPN 1 Rajeg which consist of two classes as sample, IX.G as experiment class and IX.J as control class. The IX.G used group work technique in teaching reading comprehension while IX.J used conventional method. The methodology of the research was quasi experimental design and quantitative method. The data of this research were collected by giving the test (pre-test and post-test) to the sample. The collected data were analyzed by using t-test formula. It was used to test hypothesis to know whether there is difference in reading comprehension between the students given group work technique and those given conventional method. The result of the data analysis showed that  was 4.78 higher than  1.99 with 5% of significant level. The data  was higher than   (4.78 > 1.99). It was mean that Hı was accepted while Ho was rejected. It also means that there was significance of students’ reading comprehension between students in experiment class who were taught by group work technique and the students in control class who were taught by using conventional method at SMPN 1 Rajeg. Keyword: Group Work Technique, Reading Comprehension